2018
DOI: 10.1016/j.jval.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Discrete Choice Experiment for Valuations of QLU-C10D Health States

Abstract: Results indicate that the designed DCE elicits stable health state preferences rather than guesses or mood-specific or condition-specific judgments. Nevertheless, the identified mean utility differences between test and retest need to be taken into account when determining minimal important differences for the QLU-C10D in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The wording of the DCE tasks and different layouts have been pre-tested in general population respondents which showed that although perceived difficult the tasks were considered manageable [14]. Utility weights resulting from the DCE showed to be unbiased by the ordering of attributes in the DCE [15] and stable within respondents over time [16].…”
Section: Methodsmentioning
confidence: 99%
“…The wording of the DCE tasks and different layouts have been pre-tested in general population respondents which showed that although perceived difficult the tasks were considered manageable [14]. Utility weights resulting from the DCE showed to be unbiased by the ordering of attributes in the DCE [15] and stable within respondents over time [16].…”
Section: Methodsmentioning
confidence: 99%
“…Second, participants' preferences about SARS-CoV-2 testing may change over time. Research on other topics has demonstrated that choices stated in a DCE are generally consistent, with good testretest reliability; 16,17 however, knowledge about SARS-CoV-2 and COVID-19 is rapidly evolving and is widely disseminated in mainstream media, 18 which could plausibly impact preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Second, participants’ preferences about SARS-CoV-2 testing may change over time. Research on other topics has demonstrated that choices stated in a DCE are generally consistent, with good test-retest reliability; 16,17 however, knowledge about SARS-CoV-2 and COVID-19 is rapidly evolving and is widely disseminated in mainstream media, 18 which could plausibly impact preferences. For example, reports of re-infection and the potential waning of antibodies, such as the first such report in the US in October 2020, 19 approximately one month after the completion of our DCE, might influence preferences about antibody testing, as might the availability of highly efficacious vaccines in December 2020.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when researchers conduct test-retest exercises of tasks, such as TTO, SG or choice experiments, they usually find some element of variability in the responses (Feeny et al, 2004;Gamper et al, 2018;van Agt, Essink-Bot, Krabbe, & Bonsel, 1994). In a recent study, Gamper et al (2018) found that only 25% of subjects were perfectly consistent (i.e., repeated exactly the same choice between two options) in a choice experiment. The complexity of the task has two implications for subjects' responses to TTO questions.…”
Section: Contrast Effects and Preference Imprecisionmentioning
confidence: 99%
“…The second implication is that there will be an element of variability in the evaluation of health states. Some people may change their responses to the same question from one moment to the next (Feeny et al, 2004;Gamper et al, 2018;van Agt et al, 1994). This leads to the next decision model.…”
Section: Contrast Effects and Preference Imprecisionmentioning
confidence: 99%